Sexual dimorphism in a benthic fish Oxyurichthys tentacularis (Valenciennes, 1837), Gobiidae, inhabiting Ashtamudi estuary, Kerala, India - Mohan, Remya; Sherly Williams, E. (Journal of the Bombay Natural History Society (JBNHS), 2014)
No Abstract.